دور الرقابة البيئية في استدامة الموارد الطبيعية المتمثلة بـ (الماء والهواء والتربة والمياه الجوفية) للحد من التلوث دراسة حالة معالجة الماء المصاحب لإستخراج النفط الخام - عبد الهادي منى فؤاد (Journal of Petroleum Research and Studies, 2020)
This work shows the importance of the natural resources represented by (water, air, soil and groundwater) and the importance of their sustainability that are directly related to the healthy life of living organisms on the ground with an indication of the role that the impact of human use of such resources and on the extent to which these resources are viable and sustainable for future generations. Therefore, it is necessary to find the means by which the sustainability of natural resources is maintained. Environmental monitoring is a vital tool by which stakeholders have started to maintain the sustainability of natural resources and preserve environment by activating their roles and expanding them to include all aspects of life that would preserve these resources and determine everything that would be consumed and enforced Pollution was one of the most important sources affecting the sustainability of natural resources. Midlands Oil Company as one of the important sources of pollution. Through its extractive activity of crude oil, which is injecting the reservoir (the well) with a quantity of water that varies according to the strength of the reservoir that water comes out of the oil extracted from the well, which collects in the form of polluted water bodies. Not valid for the use of living organisms, with this company and its counterparts not having comprehensive real treatments capable of confronting these water pools, by using the checklist distributed to a number of the employees of this company as well as conducting personal interviews with specialists to clarify the role of this company in pollution of the region Surrounding and view their environmental safety procedures. This issuer posed in this Research have been addressed and presented recommendation to in the light of con collusions of the theoretical study and practical application of the research being the checklist mentioned.